2009
DOI: 10.1177/1470320309352800
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme insertion/deletion and angiotensin type 1 receptor A1166C polymorphisms as genetic risk factors in benign prostatic hyperplasia and prostate cancer

Abstract: Introduction. Prostate cancer is one of the most common malignant neoplasias in developed countries. In 2003, 6,536 new cases and 4,602 related deaths were reported in Mexico. The renin-angiotensin system has been shown to play a role in prostate cancer pathology. Two previous studies investigated the association of prostate cancer with the insertion/deletion (I/D) polymorphism in the angiotensin-converting enzyme (ACE) gene; both studies reported an association between prostate cancer and the DD genotype. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Additionally, 5 case-control studies were excluded for the genotypes in control group not consistent with HWE[24-28], and 3 case-control studies were excluded for data overlapped or duplicated. Thus, a total of 25 case-control studies in 22 articles were finally identified [3-7,9,15-18,29,14,35]. The characteristics of included case-control studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, 5 case-control studies were excluded for the genotypes in control group not consistent with HWE[24-28], and 3 case-control studies were excluded for data overlapped or duplicated. Thus, a total of 25 case-control studies in 22 articles were finally identified [3-7,9,15-18,29,14,35]. The characteristics of included case-control studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Genotype and allele distributions for each case-control study are shown in Table 2. There were 8 studies of Asians [4,6,10,11,14,29,30,33], 14 of Europeans [3,5-7,9,12,13,15-17,31,32,34,35], 2 of Latinos [6,18], 1 of African-Americans [6]. In this meta-analysis, the most studied cancers were lung cancer and breast cancer, the genotype methods are a classic PCR assays…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are several studies investigating the association between ACE gene polymorphism and risk of other cancers, such as gastric cancer [31][32][33][34], colorectal cancer [21,[35][36][37], lung cancer [21,38,39], and prostate cancer [21,[40][41][42]. The results have also been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Though earlier studies suggested that this had no strong predictive value (Haiman et al 2003), more recently the DD phenotype has been associated with increased risk and poor prognosis in breast cancer (Gonzalez-Zuloeta Ladd et al 2005, Yaren et al 2007, van der Knaap et al 2008, Rosenthal & Gavras 2009). Interestingly, the same ACE polymorphism may also increase risk in benign prostatic hyperplasia (BHP) and prostate cancer, whereas the A1166C substitution in the AT1 receptor increases BHP risk alone (Sierra Diaz et al 2009). Conversely, the C allele carriers have reduced breast cancer risk (Mendizabal-Ruiz et al 2011).…”
Section: Angiotensin In Cancer Epidemiological Evidencementioning
confidence: 99%